Integrated Reporting and SDGs Disclosure: An Analysis of Factors Influencing the Quality of Integrated Reports in the Banking Sector - Nurilah, Ririn; Deprianti, Gita; Arifin, Jainal; Yusnaini, Yusnaini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the determinants influencing the quality of Integrated Reporting (IR) and Sustainable Development Goals (SDGs) disclosure in the banking sector. The growing demand for transparency and sustainability accountability has encouraged banks to adopt integrated reporting practices that combine financial and non-financial information to communicate long-term value creation. To address this issue, this study employs a Systematic Literature Review (SLR) approach based on the PRISMA guidelines to ensure a transparent and systematic literature selection process. The data were obtained exclusively from the Scopus database covering publications from 2016 to 2025. Through a rigorous screening and eligibility process, 26 empirical articles were selected and analyzed using narrative thematic synthesis. The results show that the quality of IR and SDGs disclosure in the banking sector is mainly influenced by internal governance mechanisms, including board independence, board size, gender diversity, and audit quality. In addition, firm characteristics such as bank size and profitability are identified as important determinants, as larger banks tend to have greater resources and face stronger legitimacy pressures to disclose sustainability information. External factors, particularly regulatory mandates and institutional pressures, also contribute to improving reporting quality. However, the influence of leverage and financial performance shows inconsistent results across studies. Overall, the findings indicate that integrated reporting quality reflects the interaction between governance structures, organizational resources, and institutional pressures faced by banks.